Prinsip Kepentingan Terbaik Bagi Anak Akibat Pembatalan Perkawinan Orang Tua Sedarah - Areta Edgina Apta Maharani; Agus Yudha Hernoko; Erni Agustin (Media Iuris, 2023)
Abstract Humans are created and born to live in pairs according to their life partners who have been determined by the destiny of the creator, therefore the desire for a stronger relationship is carried out through a marriage bond. Even though it has been strictly regulated by both Indonesian Marriage law and religious law, inbreeding or what is often known as incest. Incest is in fact still found in many communities. Incest is an English term that means inbreeding or discordant relationship. Inbreeding or discordant relationship is a relationship of mutual love that is sexual in nature and is carried out by couples who still have relatives or close family ties. This research aims to analyse the position of children born as a result of the annulment of incestuous marriage and to analyse the legal protection of children born as a result of the annulment of incestuous marriage. The type of research is normative research with a statutory approach and a case approach. The results show that the position of children born from incestuous marriage in civil terms despite the cancellation of marriage against both parents does not affect the status of the position of children born in the marriage and in the provisions of MUI Fatwa No.11 of 2012 provides legal protection to children born from incestuous marriage by imposing ta’zir punishment on the man who gave birth and caused his birth.